2018
DOI: 10.6008/cbpc2179-6858.2018.001.0004
|View full text |Cite
|
Sign up to set email alerts
|

Non-timber Forest Products of Mauritia flexuosa L. f.: Loss or Permanence of TEK in Quilombola Communities of Southern Amazon?

Abstract: While Non-timber forest products are relevant to conservation and development, there are diverse drivers that have a complex impact on their use and traditional ecological knowledge (TEK). The erosion of TEK and its causes were evaluated on buriti (Mauritia flexuosa L. f.) in Quilombola communities in Brazil, by using ethnographic and ethnobotanical methods, including snow ball, 23 interviews, and participant observation. Informants reported 15 different uses of buriti divided into five categories (food, anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…Both studies emphasise the ecological importance of this monodominant species in its habitat, along with other high-value species such as Virola surinamensis and Euterpe precatoria. However, our ndings also indicate a high species richness, with 112 species recorded, in contrast to the lower richness observed by Sander et al (2017) in the Juruena-Mirim Area of Relevant Ecological Interest, located in the southern Amazon region.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Both studies emphasise the ecological importance of this monodominant species in its habitat, along with other high-value species such as Virola surinamensis and Euterpe precatoria. However, our ndings also indicate a high species richness, with 112 species recorded, in contrast to the lower richness observed by Sander et al (2017) in the Juruena-Mirim Area of Relevant Ecological Interest, located in the southern Amazon region.…”
Section: Discussioncontrasting
confidence: 81%
“…A comparison of the studies by Sander (2014), Sander et al (2017) reveals that our study highlights a lower species richness in the buritizal transect (T3) speci cally, compared to other environments. This corroborates the observation by Oliveira et al (2017) about the variation in species composition in different savannah habitats.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The other included three communities (Boqueirão, Retiro, and Casalvasco Manga), close to urban areas in the transition between the Cerrado and the Amazon biome and showed that women were mainly responsible for the minimal processing of the buriti fruit into juice, sweets, and oil. In these communities, the increase in women per capita income has negatively influenced resource use (Sander et al 2018) . In the Atlantic Forest biome, Quilombola communities Cambury and Fazenda have identified, based on participatory resource assessment methodologies, cambucá (Plinia edulis) as a high-priority food resource for conservation and management of territories (Rodrigues et al 2020) .…”
Section: Discussionmentioning
confidence: 99%
“…We identified 39 Quilombola communities participating in the 24 studies reviewed. Some articles included more than one Quilombola community or more than one study; for example, Aldeia, Morro do Fortunato, and Santa Cruz, in the south of the Atlantic Forest were studied by (Ávila et al 2015, 2017) , and the Kalunga Engenho II community in the Cerrado biome was studied in more than one article (Martins et al 2012, Sander et al 2018.…”
Section: Remaining Quilombola Communities: Autonomy and Territorial M...mentioning
confidence: 99%